Assembly process planning and dynamic evaluation method based on digital twin. (25th June 2020) - Zhang, Xiangyu; Liu, Lilan; Wan, Xiang; Li, Xiaolong; Zou, Wei
In the dynamic product assembly environment, assembly process evaluation has become the key problem to improve process execution and assembly efficiency in intelligent manufacturing mode. For this reason, the assembly process planning and dynamic evaluation method driven by digital twin is proposed. Based on the five-dimensional model, the architecture of assembly process digital twin system is established, facing with ergonomics, the digital twin modeling and optimization of all elements of "human-machine-object-environment" in workshop assembly process was completed, the expression model and perception framework of assembly process real-time data are created, and the real-time mapping logic structure of assembly workshop operation is put forward, and the twin data of assembly process evaluation are created. The dynamic evaluation process of assembly process driven by twin data is described and then the validity of the proposed method is verified by an example of a car rear axle assembly process.